Strengthening the Fund's Ability to Assist Low-Income Countries Meet Balance of Payments Needs Arising from Sudden and Exogenous Shocks : Supplement. (Policy Papers; Policy Paper ;, 2005)
The G-8 debt relief proposal, if adopted, should have little impact on the rational and operational aspects of the shocks window, but it may affect some of the financing consideratins, which are taken up in the page on "The G-8 Debt Cancellation Proposal and its Implications for the Fund.